Heterometallic Co–Dy SMMs grafted on iron oxide nanoparticles. Issue 27 (23rd June 2021) - Rosado Piquer, Lidia; Dreiser, Jan; Sañudo, E. Carolina
Abstract : Molecular spintronic applications require that SMMs remain intact and retain their magnetic properties when deposited on a substrate. An organic spacer between the SMM and magnetic surface helps the SMM retain its magnetic properties on the surface. Abstract : Heterometallic 3d–4f SMM [Co4 Dy(OH)2 (SALOH)5 (chp)4 (MeCN)(H2 O)2 ] (1 ) has been deposited onto iron oxide nanoparticles (NPs ) with an oleate self-assembled monolayer (SAM) as a surfactant. The obtained hybrid molecular-inorganic system 1-NP has been thoroughly characterized. The oleate SAM separates SMM 1 from the magnetic substrate to avoid the strong-coupling between the surface and molecule to ensure that 1 retains its magnetic properties in 1-NP . The magnetic properties of the hybrid system 1-NP have been characterized by element specific XMCD: the heterometallic SMM retains its magnetic properties on the surface of the iron oxide NPs while there is an enhancement of the magnetic properties of the NP s.